Simulation and experimental study on olive drop injury - Weike Lan; Haotian Mu; Di Xin; Shijia Pan; Yuncai Yan; Wen Gao; Zijie Niu; Dongyan Zhang; Jun Zhang; Yongjie Cui (Smart Agricultural Technology)
Inadequate harvesting and post-harvest handling of olives can damage the fruit and seriously affect the quality of the extracted oil. In this study, vibration harvesting drop tests and finite element simulations were performed on the olive variety ''Leccio'' to optimize the collision parameters to evaluate and predict the damage level and damage resistance of olives. The physical properties of olives were first determined using compression tests and other physical measurements, and the damaged area was assessed by performing drop tests in a laboratory environment and considering a variety of contact materials. Second, a three-dimensional model of oil olives was established by reverse engineering, and collision simulations with different heights, multiple collision angles, and different contact materials were carried out in finite elements to obtain the damage volume, energy, and damage susceptibility. The stress magnitude, distribution, and energy changes during collision contact were analyzed and combined with experimental data to obtain the relationship between the damage volume and damage area with high determination coefficients by fitting. Finally, the response surface method was used to analyze the effect of fall height, contact material, and collision angle on the damage volume, and the best collision parameters were obtained. The drop test data showed that the damaged area of the olive increases gradually with an increase in fall height, the damage area of a drop on cushioning material is smaller than that on non-cushioning material, and the damage areas produced by different drop angles are different. The optimum fall height was below 1.05 m, the contact material was a foam board, and the collision angle was 49.05 °. When the damage volume was less than 2.75 mm3, the finite element simulation results showed that the damage volume under this optimal parameter was less than 2.59 mm3, with an error of 6.2%. These results show that the simulation of collision behavior and prediction of damage to olives using finite element simulation are reliable, and this study can provide a theoretical basis for the optimization of olive fruit harvesting and post-harvest handling methods.